TRADISI BUWUHAN SAAT WALIMATUL ‘URSY PERSPEKTIF MASLAHAH MURSALAH - Ulfati, Mazida; Qurotul Aini, Siti Maryam (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
The term buwuh is a tradition of helping each other for people celebrating weddings. The buwuhan tradition has been going on for generations and is still maintained by the community. The implementation of buwuh begins with neighbors gathering at a celebration event to provide assistance. This assistance can be in the form of money, basic necessities, energy, thoughts and so on. This tradition aims to help each other and strengthen ties of brotherhood. In Maslahah Mursalah's view, this tradition has a positive impact, namely the implementation of the teachings of mutual help and as a feeling of empathy for family and neighbors who are holding a celebration. The buwuhan tradition is generally carried out at walimatul ursy or wedding parties by bringing rice, sugar, oil, noodles and other food ingredients. The buwuhan tradition when attending Walimatul Ursy is included in the category of Al-Maslahah al-Tahsiniyat (benefits that are complementary in nature) in terms of importance and quality, while in terms of its existence it is included in the category of Al-Maslahah Al-Mursalat (benefits that are not mentioned by the text either in denial or recognition) p. This can be used as a source of evidence for Islamic law, because it meets the requirements and brings benefits to all.